Comprehensive Earthquake Catalogs and Seismicity Parameters from Incomplete Earthquake Catalogs of Guilan Region, Iran - Ali Ghorbani; Ardavan Izadi (Salehan Institute of Higher Education, 2017)
Statistics of human losses and financial casualties in Guilan province as one of the most populated and strategic areas in the north of Iran have doubled the importance of having knowledge about earthquake and strategies to reduce its effect. In order to investigate seismic hazard analysis, earthquake records along with selecting the proper distance of intended locations were gathered to make Poissonian catalogs. The earthquake catalogs cover the geographical area limited to 35.0°-39.3°N, 47.1-52.2°E and include around 4,000 earthquake events between the years of 855 to 2016. An extensive amount of efforts and times are required to eliminate duplicated events, to unify the magnitude scales and to cluster the earthquake sequences with variable windows in time and location domains to remove aftershocks and foreshocks. The Final homogenous catalog consists of around 110 events for each region. Magnitude of completeness in different time intervals is reported for Guilan region. Seismicity parameters were achieved using Gutenberg-Richter method by Zmap and Kijko-Sellovell approaches for important cities of Guilan including Rasht, Anzali, Rudbar, and Lahijan. Comparative analysis of the results from Zmap and Kijko-Sellovell approaches shows good consistency in the estimation of seismic parameters with the result of literature.